PENGELOLAAN EKSTRAKURIKULER OLAHRAGA FUTSAL SMA NEGERI DI KOTA SEMARANG TAHUN 2020 - Denhas, Jelang Surya (Universitas Negeri Semarang, 2021)
The city of Semarang has been known as one of the cities that has people with very high enthusiasm forfutsal. The large number of futsal fans will certainly invite interest and desire to hold a match. Futsalmatches are also often held in schools, universities, or other institutions. This study uses a descriptiveresearch approach with qualitative methods. Data collection using data triangulation method consisting ofobservation, interviews, and documentation. The instruments used are interview and documentationinstruments. The data analysis model in this study is SWOT analysis. The results and conclusions of thestudy are as follows: Strength: the sports facilities available in most schools are adequate, Weakness: someschools do not have futsal extracurricular equipment that meets quality training standards, Opportunities:giving rewards or awards from schools to students who excel, as Threat: decreased achievement becausethere is no futsal competition. Suggestions are given as follows: There is a need for reports and evaluationsrelated to futsal extracurriculars, it is necessary to improve or add futsal extracurricular facilities andequipment, hold futsal competitions as often as possible so that achievement does not decrease, and recruitfutsal coaches who have coaching certifications